Acceptance of Malaysian halal certification and Malaysia as halal hub by OIC-member food manufacturers - Abdul Rahman, Rozailin (2014)
Malaysia, being a model Islamic nation is well poised to contribute to everincreasing Halal industry. Being a member of the Organization of Islamic Cooperation (OIC), Malaysia is pushing its Halal certification, the only logo in the world that is supported by its government, as an international standardized logo to be used by all Muslim nations. This move is currently being supported by the majority of OIC members, but other countries such as Turkey, Pakistan and Abu Dhabi are also starting to show their interest in promoting their own Halal logo to be used by the OIC members and to become the Halal hub for the OIC member countries. Therefore an important question is whether or not the food manufacturers in the Islamic countries see this standard as necessary, and if so, certification and logo from which country is most preferred for application in their businesses. Thus it is inevitable to gauge the acceptance of Malaysian Halal certification and Malaysia as Halal hub from the OIC food manufactures’ perspective. The study uses data collected from a structured questionnaire survey that was distributed to 300 OIC Halal food manufacturers during two different Halal promotional events and an online survey. The samples were collected from 57 OIC countries. Descriptive statistics, factor analysis and Structural Equation Modelling (SEM) were used to analyze the information gathered from the questionnaires. The results suggested Malaysia itself in term of strategic location, expertise in Halal research development and it background in Halal are the direct measure of the food manufacturers’ attitude to accept Malaysian Halal Certification and Malaysia as Halal Hub among themselves. Furthermore, the influence of perceived behavioral control including the processing fees, information exposure and government incentives make them more aware about trusted Halal certification.